Longitudinal associations of gross motor development, motor milestone achievement and weight-for-length z score in a racially diverse cohort of US infants. Issue 1 (15th January 2019) - Shoaibi, Azza; Neelon, Brian; Østbye, Truls; Benjamin-Neelon, Sara E
Abstract : Objectives: To investigate longitudinal associations between gross motor development, motor milestone achievement and weight-for-length z scores in a sample of infants. In a secondary aim, we explored potential bidirectional relationships, as higher weight-for-length z scores may impede motor development, and poor motor development may lead to obesity. Design: The design was an observational birth cohort. Setting: We used data from the Nurture study, a birth cohort of predominately black women and their infants residing in the Southeastern USA. Participants: 666 women enrolled their infants in Nurture. We excluded infants with missing data on exposure, outcome or main covariates, leaving a total analytic sample of 425 infants. Primary outcome: The outcome was weight-for-length z score, measured when infants were 3, 6, 9 12 months. Results: Among infants, 64.7% were black, 18.8% were white and 16.9% were other/multiple race. Mean (SD) breastfeeding duration was 17.6 (19.7) weeks. Just over one-third (38.5%) had an annual household income of < $20 000. After adjusting for potential confounders, higher motor development score was associated with lower weight-for-length z score (−0.004; 95% CI −0.001 to –0.007; p=0.01), mainly driven by associations among boys (−0.007; 95% CI −0.014 to –0.001; p=0.03) and not girls (0.001; 95% CI −0.005 to 0.008; p=0.62). Earlier crawling was the only milestone associated with a lower weight-for-length z score at 12 months (−0.328; 95% CI −0.585 to 0.072; p=0.012). However, this association appeared to be driven by male infants only (−0.461; 95% CI −0.825 to −0.096; p=0.01). Weight-for-length z score was unrelated to subsequent motor development score and was thus not bidirectional in our sample. Conclusions: Higher motor development score and earlier crawling were associated with lower subsequent weight-for-length z score. However, this was primary true for male infants only. These findings contribute to the growing body of evidence suggesting that delayed motor development may be associated with later obesity.